COVID-19: PSYCHOLOGICAL TIPS FOR ALL - Naveed Shibli; Tariq Rashid; Ali Sher (Journal of University Medical & Dental College, 2021)
BACKGROUND & OBJECTIVE: The world is facing a COVID-19 pandemic. The cure for the disease is yet to be established. This situation has created a severe stress-producing challenge for humankind. It has been reported in few studies that human health and adaptability are dependent on and are related to hope level. How this connection could help humanity to face the COVID-19 challenge was the main focus of the present work. METHODOLOGY: A library research was conducted to explore the individual potential to increase ’hope’ and to evolve specialized instructions (tips) that could help to improve pandemic stress coping: It was convincing that increase in level of hope with due watchfulness is possible, that could contribute towards improving coping in the prevailing challenging, stressful situation. RESULTS: To exercise ‘tips’ to improve hope was found psychologically possible. It was also convincing that ‘tips’ by improving the ‘hope’ level would add to the surviving spirit and subsequent coping. CONCLUSION: Exercising ‘tips’ would improve pandemic stress coping.